2015
DOI: 10.1037/a0039801
|View full text |Cite
|
Sign up to set email alerts
|

Thirst for knowledge: The effects of curiosity and interest on memory in younger and older adults.

Abstract: Given age-related memory impairments, one’s level of curiosity or interest could enhance memory for certain information. In the current study, younger and older adults read trivia questions, rated how curious they were to learn each answer, provided confidence and interest ratings, and judgments of learning (JOL) after learning the answer. No age-related differences in memory were found. Analyses indicated that curiosity and interest contributed to the formation of JOLs. Additionally, interest had a unique inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
113
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 34 publications
14
113
0
Order By: Relevance
“…The momentary experience of curiosity can be seen as a motivational state that facilitates knowledge acquisition (Silvia & Kashdan, 2009; Gottlieb and Oudeyer, 2018). Consistent with this idea, studies have shown that states of high curiosity enhance long-term memory (Kang et al, 2009; Gruber et al, 2014; McGillivray et al, 2015; Marvin and Shohamy, 2016; Stare et al, 2018; Galli et al, 2018). Furthermore, recent neuroimaging evidence suggests that state curiosity enhances memory via increased activation in the mesolimbic dopaminergic circuit including the hippocampus (Gruber et al, 2014; Kang et al, 2009).…”
Section: Introductionmentioning
confidence: 75%
“…The momentary experience of curiosity can be seen as a motivational state that facilitates knowledge acquisition (Silvia & Kashdan, 2009; Gottlieb and Oudeyer, 2018). Consistent with this idea, studies have shown that states of high curiosity enhance long-term memory (Kang et al, 2009; Gruber et al, 2014; McGillivray et al, 2015; Marvin and Shohamy, 2016; Stare et al, 2018; Galli et al, 2018). Furthermore, recent neuroimaging evidence suggests that state curiosity enhances memory via increased activation in the mesolimbic dopaminergic circuit including the hippocampus (Gruber et al, 2014; Kang et al, 2009).…”
Section: Introductionmentioning
confidence: 75%
“…Thus, IPEs reflect the discrepancy between the actual value of the presented information relative to the participants' initial curiosity expectation. To examine the interactive effects of curiosity and IPE, we performed linear mixed-level analyses on trial-level data (see Marvin & Shohamy, 2016;McGillivray et al, 2015). Mixed-effect models allow within-person examination of curiosity and surprise effects with more fine-grained distinctions between levels of curiosity and IPE, while at the same time accounting for variability across participants.…”
Section: Behavioral Analysesmentioning
confidence: 99%
“…In addition to these benefits, the subjective interestingness or surprise associated with the actual information also affects later memory (Fastrich, Kerr, Castel, & Murayama, 2018;Marvin & Shohamy, 2016;McGillivray, Murayama, & Castel, 2015). For example, Marvin and Shohamy (2016) calculated information prediction errors (IPEs) which reflect the difference between the subjective interestingness associated with the information and the initial curiosity about the information.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations